PENERAPAN STRATEGI PEMBELAJARAN AKTIF SEPAK BOLA VERBAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 1 KAMPAR TIMUR - Andayanis '; Elva Yasmi Amran; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : It has been done of research with applied the active learning strategy of Football Verbal that aims to improve student learning achievement on the topic of Colloid in class XI science of Senior High School Number1 Kampar Timur. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class XI IPA2 as the experimental class and students of class XI IPA3 as the control class randomly selected after homogeneity test. Experimental class is a class which was given a treatment by applying active learning strategy of Football Verbal in learning process. Data analysis technique used is the t-test with α = 0,05. Based on the result of data analysis, it obtained tcount> ttable which is 3,74>1,67. The results showed that the application of active learning strategy of Football Verbal can improve student learning achievement on the topic of Colloid in class XI science of Senior High School Number 1 Kampar Timur. Improved learning achievement can be seen from the coefficient of the effect achieved is 18,91%.Keywords: Active Learning Strategy of Football Verbal, Learning Achievement, Colloid